VITOSTEROID-PRESERVING MEDICINAL PLANTS AND THEIR IMPORTANCE IN MEDICINE (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Medicinal plants - for the treatment of humans and animals, for the prevention of diseases, as well as plants used in the food, perfume and cosmetic industry. On earth there are 1000 species of medicinal plants. Of these, in natural conditions in Uzbekistan about 120 species of plants grown and cultivated in scientific and folk medicine. This article provides information about medicinal plants containing phytosteroids and their importance in medicine.